1997
DOI: 10.1002/hlca.19970800602
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective Ring Opening of Electronically Excited Cyclohexa‐2, 4‐dienones: Cause and effect

Abstract: The two conformers of a cyclohexa‐2, 4‐dienone with different substituents at C(6) on irradiation are believed to undergo ring opening stereospecifically affording a mixture of two configurationally isomeric diene‐ketenes (and descendents thereof)‐ Exceptions are generally found for those dienones with one C and one O substituent or even with two C substituents, if one of them carries a polar group at a site able to interact through space with the ring CO group. In these cases, only one of the two anticipated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 57 publications
2
8
0
Order By: Relevance
“…The acyclic ester products 3a and 3b are at the same oxidation state as the starting materials but correspond to the addition of 2 equiv of methanol, and their formation requires a reaction mechanism involving cleavage of the C−C bond between the oxygenated carbons C-1 and C-6, analogous to intradiol catechol cleavage. The same reaction products were observed when the reaction was carried out in the dark, thus ruling out a photochemical reaction, which has been observed for other 2,4-cyclohexadienones …”
Section: Resultssupporting
confidence: 77%
“…The acyclic ester products 3a and 3b are at the same oxidation state as the starting materials but correspond to the addition of 2 equiv of methanol, and their formation requires a reaction mechanism involving cleavage of the C−C bond between the oxygenated carbons C-1 and C-6, analogous to intradiol catechol cleavage. The same reaction products were observed when the reaction was carried out in the dark, thus ruling out a photochemical reaction, which has been observed for other 2,4-cyclohexadienones …”
Section: Resultssupporting
confidence: 77%
“…It has been suggested that oxyallyl compounds are intermediates in both thermal and photochemical rearrangements of bicyclo[3.1.0]hex-3-en-2-ones to phenols [25][26][27][28][29][30][31][32][33][34][35]. Some time ago, we studied the reaction pathway for the prototype rearrangement of bicyclo[3.1.0] hex-3-en-2-one (1a) to phenol (3a) in the gas phase at the CASSCF/CASPT2 level [36].…”
Section: Introductionmentioning
confidence: 99%
“…Besides these natural products, several compounds with the same bicyclic structure have been prepared, most commonly by photorearrangement of cyclohexenones, phenols, or cyclohexadienones . The latter transformation, originally found in the conversion of santonin to lumisantonin, has been the subject of extensive mechanistic studies , Much less information is known about the photochemical rearrangement of bicyclo[3.1.0]hex-3-en-2-ones into phenols, which was observed by Eastman in 1959 when he reported that the irradiation of neat umbellulone ( 1 ) gave thymol ( 2 ) (Scheme ). The difficult availability of these bicyclic compounds has reduced the study of their photochemical behavior to few cases .…”
mentioning
confidence: 99%